2010
DOI: 10.1074/jbc.m110.128835
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Lamin A, Bypassing Prelamin A Processing, Causes Misshapen Nuclei in Fibroblasts but No Detectable Pathology in Mice

Abstract: Lamin A, a key component of the nuclear lamina, is generated from prelamin A by four post-translational processing steps: farnesylation, endoproteolytic release of the last three amino acids of the protein, methylation of the C-terminal farnesylcysteine, and finally, endoproteolytic release of the last 15 amino acids of the protein (including the farnesylcysteine methyl ester). The last cleavage step, mediated by ZMPSTE24, releases mature lamin A. This processing scheme has been conserved through vertebrate ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 41 publications
3
89
1
Order By: Relevance
“…To test this idea, we examined lamin A expression in Lmna LAO/LAO mice in which all the output of the Lmna gene is channeled into the production of mutant prelamin A transcripts encoding mature lamin A (18). Because lamin C splicing is absent in these mice, we expected to find increased levels of lamin A in the brain (i.e., levels comparable to lamin C levels in the brain of wild-type mice).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this idea, we examined lamin A expression in Lmna LAO/LAO mice in which all the output of the Lmna gene is channeled into the production of mutant prelamin A transcripts encoding mature lamin A (18). Because lamin C splicing is absent in these mice, we expected to find increased levels of lamin A in the brain (i.e., levels comparable to lamin C levels in the brain of wild-type mice).…”
Section: Resultsmentioning
confidence: 99%
“…The intensities of the lamin C bands in the brain were similar to those in the kidney, but the prelamin A bands were faint. We also examined transcripts in two Lmna knockin mice- Lmna LAO/LAO mice that express exclusively mutant prelamin A transcripts encoding mature lamin A (18) and Lmna nHG/nHG mice that express mutant prelamin A transcripts encoding nonfarnesylated progerin (Materials and Methods) (12). Lamin C transcripts were absent, as expected, in both knockin models, but, similar to wild-type mice, the levels of prelamin A transcripts were much lower in the brain than in the kidney (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier in vitro studies had suggested that prelamin A prenylation is important for lamin A function and its delivery to the nuclear rim (27)(28)(29), but recent studies with knock-in mouse models have suggested otherwise. Coffinier et al (30) created knock-in mice that produce mature lamin A directly, bypassing prelamin A synthesis and farnesylation. The "mature lamin A" mice were healthy and fertile, and the lamin A in their tissues was positioned normally along the rim of the cell nucleus, indistinguishable from lamin A in the tissues of wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of prelamin A, cell culture studies suggested that protein farnesylation plays a vital role in the targeting of prelamin A to the nuclear rim (27)(28)(29), but recent studies with gene-targeted mice have raised questions about the in vivo relevance of those findings. For example, knock-in mice that produce mature lamin A directly (bypassing prelamin A synthesis and protein farnesylation) are free of disease, and the nuclear rim positioning of lamin A in the tissues of mice is quite normal (30).…”
mentioning
confidence: 99%